2009
DOI: 10.1111/j.1548-1352.2009.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Side by Side: Learning by Observing and Pitching In

Abstract: This article examines cultural practices that support informal learning as children observe and pitch in with everyday activities that are integrated into family and community life. We discuss the social and cultural grounding of this learning tradition, drawing on research carried out in different parts of the world during more than 60 years. Children learn by watching, listening, and attending, often with great concentration, by taking purposeful initiative, and by contributing and collaborating. We try to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
224
0
46

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(288 citation statements)
references
References 31 publications
2
224
0
46
Order By: Relevance
“…According to Kline's classification, culture-based definitions of teaching concern activities in classrooms in modern societies, in contrast to informal learning in traditional societies (Lancy 2010;Paradise and Rogoff 2009). From our point of view, classroom teaching is less interesting, since it is a comparatively recent phenomenon and does not give much insight into the evolutionary roots of teaching.…”
Section: Three Kinds Of Definitionsmentioning
confidence: 91%
“…According to Kline's classification, culture-based definitions of teaching concern activities in classrooms in modern societies, in contrast to informal learning in traditional societies (Lancy 2010;Paradise and Rogoff 2009). From our point of view, classroom teaching is less interesting, since it is a comparatively recent phenomenon and does not give much insight into the evolutionary roots of teaching.…”
Section: Three Kinds Of Definitionsmentioning
confidence: 91%
“…In the cosleeping study, forager parents indicated that their children slept wherever they wanted, whereas the farmer parents said that they told their children where to sleep. Recent studies in social anthropology on informal learning emphasize self-motivation [27], but hunter -gatherer children probably initiate learning and discovery more often than children in other modes of production. Forager children's high motivation to learn occurs early and often.…”
Section: Cultural and Demographic Contexts Of Congo Basin Hunter -Gatmentioning
confidence: 99%
“…The first section of a recent review of children's social learning by social anthropologists Lancy & Grove [25] is titled 'The absence of teaching'. Like many social anthropologists, they indicate that teaching seldom occurs in small-scale cultures and emphasize the importance of observational [26] and informal learning [27]. MacDonald's [24] hunter-gatherer study also concluded that 'teaching is unimportant'.…”
Section: Introductionmentioning
confidence: 99%
“…Imitation also relies on the learners' ability to adopt the visual perspective of others, in order to understand their actions [49][50][51]. Children's learning by imitation in various human societies has a wide range of forms [52] such as helping with daily tasks [53] or third-party observation [40]. The learner's position with respect to the demonstrator(s) will vary in different situations.…”
Section: Introductionmentioning
confidence: 99%